The Role of Monetary Policy in Israel's 1985 Stabilization Effort. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
Comparing the performances of the Austral, Cruzado and Sheqel programs shows that the latent suggestion that a 'heterodox' stabilization program can be implemented without tight fiscal discipline to support a restrictive monetary policy, though welcome in the politicial arena, is unwarranted. Freezes, pegs and controls alone are bound to lead to dismal failure. A highly restrictive monetary policy sustained by a tight fiscal policy persisting for a lengthy interval (in terms of the political horizon), supported by a stable exchange rate as a highly visible nominal anchor and by a temporary but significant erosion of real wages, have succeeded to contain a runaway inflation in Israel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet